Perlindungan Hukum Terhadap Hak-Hak Pekerja Migran Indonesia Sektor Rumah Tangga - Amira Hasna Nabila (Jurist-Diction, 2022)
AbstractThe majority of Indonesian migrant workers who work in the domestic sector are women. As a result, they are vulnerable to cases such as torture, violence, sexuality, and physical and emotional exploitation. In Indonesia, the rule of law against Indonesian Migrant Workers is regulated in Law Number 18 of 2017 concerning the Protection of Indonesian Migrant Workers. However, the existence of this regulation does not specifically apply to non-procedural Indonesian Migrant Workers in the Household Sector who are victims of human trafficking. Every Indonesian Migrant Worker, whether procedural or not, has the right to be protected as part of an Indonesian citizen. Non-procedural Indonesian Migrant Workers in the Domestic Sector are entitled to legal protection in a preventive and repressive manner.Keywords: Legal Protection; Indonesian Migrant Workers; Domestic Workers.AbstrakPekerja Migran Indonesia khususnya yang bekerja pada Sektor Rumah Tangga mayoritasnya adalah perempuan. Akibatnya, mereka rentan mengalami kasus-kasus seperti penyiksaan, kekerasan, seksual, dan eksploitasi fisik serta emosional. Di Indonesia, aturan hukum terhadap Pekerja Migran Indonesia diatur dalam Undang-Undang Nomor 18 Tahun 2017 Tentang Perlindungan Pekerja Migran Indonesia. Namun, adanya aturan ini belum mengatur secara khusus terhadap Pekerja Migran Indonesia Sektor Rumah Tangga non prosedural yang menjadi korban perdagangan orang. Setiap Pekerja Migran Indonesia baik prosedural maupun tidak mempunyai hak untuk dilindungi sebagai bagian dari warga negara Indonesia. Pekerja Migran Indonesia Sektor Rumah Tangga non prosedural berhak untuk mendapatkan perlindungan hukum secara preventif dan represif.Kata Kunci: Perlindungan Hukum; Pekerja Migran Indonesia;Pekerja Sektor Rumah Tangga.